A survey-based assessment of attitudes and needs regarding tinnitus healthcare among patients and healthcare professionals in Europe - Steinmetzger, Kurt; Schiele, Tabea; Boecking, Benjamin; Avraamides, Marios; Bamidis, Panagiotis D.; Basso, Laura; Dobel, Christian; Gilou, Sotiria; Ioannou, Christos I.; Shimi, Andria; Vellidou, Eleftheria; Paraskevopoulos, Evangelos; et al. (Frontiers in Audiology and Otology, 2024)
Despite good agreement of national guidelines for the assessment and treatment of tinnitus, there is still substantial variation regarding tinnitus-related healthcare across Europe. In contrast to previous work, which has mainly focussed on the perspective of healthcare professionals, we here report the results of separate web-based surveys conducted with clinicians and researchers as well as tinnitus patients. These surveys were devised to obtain information about their respective attitudes and needs with respect to tinnitus healthcare, and to reveal possible interdisciplinary inconsistencies among clinicians and researchers. We mainly targeted participants from Germany, Cyprus, and Greece, the countries in which the institutions of the researchers involved in this project are based. Results showed, firstly, that the treatment satisfaction of the patients was overall more negative than that of the clinicians and researchers, and that the patients' treatment satisfaction did not depend on the number of different treatments they had received. Secondly, patients as well as clinicians and researchers indicated that they were interested in learning more about a variety of tinnitus-related topics, especially treatment strategies, with no marked differences between clinicians from different professional disciplines. This suggests similar tinnitus-specific educational needs in patients and healthcare professionals.